Model Pembelajaran Kooperatif: Apakah efektif untuk meningkatkan motivasi belajar peserta didik? - Baso Intang Sappaile; Zuhad Ahmad; I Putu Agus Dharma Hita; Geofakta Razali; RD. D. Lokita Pramesti Dewi; Ratna Novita Punggeti (Journal on Education, 2023)
This research aims to examine the influence of Cooperative Learning Model on students' learning motivation through literature review. High learning motivation is an important factor in enhancing students' engagement and achievement. The Cooperative Learning Model is the focus of this study as it emphasizes cooperation and social interaction among students. The research method used is literature review, by searching and analyzing relevant sources regarding the influence of Cooperative Learning Model on students' learning motivation. Based on the findings of the literature review, the Cooperative Learning Model has great potential in improving students' learning motivation. Students who are engaged in cooperative learning tend to exhibit higher motivation, active engagement, and greater interest in the subject matter. The effective implementation of the Cooperative Learning Model in enhancing students' learning motivation can be influenced by factors such as group size, interaction among group members, the role of the teacher, and the support from the learning environment. Therefore, it is important to consider these factors in designing and implementing the Cooperative Learning Model. This research provides a comprehensive understanding of the influence of the Cooperative Learning Model on students' learning motivation through literature review. Practical implications and future research directions are also discussed to provide guidance in the application and further exploration of the Cooperative Learning Model. The results of this research are expected to contribute positively to efforts in enhancing students' learning motivation.